Imersão e presença nos jogos FPS: uma aproximação qualitativa - Sousa, Carlos Augusto Pinheiro de (2012)
This research aims to investigate immersion and presence in FPS as qualitative approach. This investigation is done by taking in account the two decades of successes on the FPS genre in the games industry in which has been observed paradigm transformations that include control mappings, depth of interaction, graphic realism, considerable expansion in multi-user environments etc. The methodology has been an heuristic one with such an ontological focus situated between the relations of the specific FPS genre and virtual reality done by an organization of bibliographic references and a discussion with professionals from the international industry. From the selected survey which has been organized and selected as a qualitative approach withing the academic literature in both virtual reality and digital games to establish a synthesis of factors to be observed in case studies and evaluated by invited developers from the FPS games industry. This way, it relates the concepts, situating immersion in the field of the convincing experience of the game and that of being in the game . In parallel, the term virtual reality (as a support), by which multi-form definitions emplaces it between device configurations or setups related to sensorial perception and of psychological experiences provided by this medium, the extra-sensorial reach, reflects the development of a projected immersive reproduction by which users of this medium describe the sense of presence, of being in another place or another world. It is believed that the result of this work should contribute to fulfill of studies in the specific FPS genre field, within the own virtual reality studies and possibly in the aiding of design for the development of the FPS games